Meningkatkan Kualitas Pendidikan Melalui Sistem Pembelajaran yang Tepat Di Desa Tiram - Drista, Vera Nita (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2022)
Education has entered a new beginning in the world of education. Equitable and quality education is determined by the quality and competence of educators in the family, school, and community environment. Improving the quality of education is an integrated process with the process of improving the quality of human resources itself. Education is not only for individual or personal interests, but also for the benefit of the community, especially the village community. In this case, especially the people of the village of Tiram. Oyster Village is one of the villages in the Bangka Belitung Islands Province, South Bangka Regency, precisely in Tukak Sadai District. From the work program that has been mutually agreed, especially in the field of education, it has been implemented in accordance with the identification of problems in Tiram Village. The purpose of identifying these problems is to improve the quality of education in schools in Tiram Village. One of the work programs that have been implemented is implementing a reading literacy program for all children by utilizing the existing library in Tiram Village and the school library as a learning system in improving the quality of student education. Pendidikan telah memasuki awal bar dalam dunia pendidikan. Pendidikan yang merata dan berkualitas ditentukan oleh kualitas dan kompetensi pendidik dalam lingkungan keluarga, sekolah, dan masyarakat. Peningkatan kualitas pendidikan merupakan suatu porses yang terintegrasi dengan proses peningkatan kualitas sumber daya manusia itu sendiri. Pendidikan tidak hanya untuk kepentingan individu atau pribadi saja, tetapi juga untuk kepentingan masyarakat terlebih lagi masyarakat desa. Dalam hal ini, khususnya masyarakat Desa Tiram. Desa Tiram merupakan salah satu desa yang berada di wilayah Provinsi Kepulauan Bangka Belitung, Kabupaten Bangka Selatan tepatnya di Kecamatan Tukak Sadai. Dari program kerja yang telah disepakati bersama khususnya di bidang pendidikan telah dilaksanakan sesuai dengan identifikasi masalah di Desa Tiram. Tujuan mengidentifikasi masalah tersebut guna meningkatkan kualitas pendidikan di sekolah-sekolah yang ada di Desa Tiram. Salah satu program kerja yang telah dilaksanakan ialah menerapkan program literasi membaca bagi seluruh anak-anak dengan memanfaatkan perpustakaan yang ada di Desa Tiram dan perpustakaan sekolah sebagai sistem pembelajaran dalam meningkatkan kualitas pendidikan peserta didik.